A Study of References in Mining Engineering Publications. - Linda Musser (Issues in Science and Technology Librarianship, 2007)
The article presents the findings of a study that examines references from mining engineering publications and contrasts the results with those from the 1996 study of the characteristics of the engineering literature. It notes that a total of 862 references were examined for the study. It cites the similarity of the age distribution of references in the study and that of the 1996 research. It explores the implications of the study for managers with collections of mining engineering materials.